A low temperature approach for photo/cathodoluminescent Gd2O2S:Tb (GOS:Tb) nanophosphors. Issue 6 (21st December 2018) - Wang, Xuejiao; Meng, Qinghong; Li, Meiting; Wang, Xiaojun; Wang, Zhihao; Zhu, Qi; Li, Ji‐Guang
Abstract: Titrating the aqueous solution of equimolar RE(NO3 )3 and (NH4 )2 SO4 with NH4 OH to pH~9 at ~4°C produced an amorphous precursor that yielded phase‐pure and well‐dispersed RE2 O2 S nanopowder (RE = Gd0.99 Tb0.01 ; GOS:Tb) via a RE2 O2 SO4 intermediate upon annealing in H2 . The powders calcined at the typical temperatures of 700/1200°C exhibited unimodal size distributions and have the average crystallize sizes of ~17/55 nm, average particle sizes of ~284/420 nm, and specific surface areas of ~14.62/4.53 m 2 /g (equivalent particle sizes: ~56/180 nm). The 1200°C product exhibited sharp green luminescence at ~544 nm (FWHM = 2.3 nm; λ ex  = 275 nm), with an absolute quantum yield of ~24.8% and a fluorescence lifetime of ~1.34 ms at room temperature. It was also shown that the powder possesses favorable thermal stability (the activation energy for thermal quenching of luminescence ~0.305 eV) and is stable under electron beam irradiation up to 7 kV and 50 μA. The synthetic technique has the advantages of scalability and favorable dispersion and high chemical/phase purity for GOS powder, which may allow the sintering of scintillation ceramics at lower temperatures. Abstract : Gd2 O2 S:Tb nanophosphor with favorable dispersion and high chemical/phase purity was obtained via a low temperature precipitation approach.